Industrial Relations: A Paradigmatic Analysis - Young, Stanley (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
After noting some of the differences between paradigmatic and normal research, the author suggests, as has occurred with other disciplines, the need for industrial relations paradigmatic research.